Challenges and Solutions to Local Culture of South Sulawesi in the Era of Globalization - Andi Quarzy Ayatullah; Abu Haif; Fitri Maylan Haq; Nurhaerat Nurhaerat; Zulfikar Zulfikar; Sulkifli Sulkifli; Husni Mubarak; Elsa Wildia Bahar (Institut Agama Islam Al-Fatimah Bojonegoro, 2024)
This article aims to investigate local cultural problems in the era of globalization, especially in South Sulawesi, and analyze the challenges and relevant solutions to dealing with these problems in the era of globalization. One of the factors causing local culture to be forgotten nowadays is the lack of interest or desire in the next generation to learn and inherit their own culture. Apart from that, the influence of globalization in this era has had a huge impact on society, especially local culture., in South Sulawesi itself. Therefore, the aim of writing this article is to present the challenges and solutions for preserving local culture in the era of globalization. The method used is a qualitative method with descriptive analysis. According to Malinowski, a higher and more active culture will influence a lower and more passive culture through cultural contact. This theory is very visible in the shift in cultural values, which, in the era of globalization, has become a very powerful force in influencing people's thinking patterns. To overcome this, it is necessary to be aware of the importance of local culture as a characteristic of a particular region or nation. Every level of society must preserve it, where the role of the younger generation is highly expected to continue trying to inherit local culture and will be a strength for the existence of local culture itself even though it is hit by the current of globalization